PENGARUH INFLASI, SUKU BUNGA DAN NILAI TUKAR TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PADA PERIODE 2013-2016 - Sitanggang, Hotmauli; Munthe, Kornel (UNIKA Santo Thomas, 2018)
This study aims to analyze and determine the effect of inflation, interest rates and exchange rates on stock returns on manufacturing companies that go public on the Indonesia Stock Exchange in the 2013-2014 period. The population in this study were 149 companies that went public on the Indonesia Stock Exchange in 2013-2016. By using the Slovin method, a sample of 60 companies was obtained. This type of data is secondary data obtained by documentation techniques. The data analysis technique used is multiple linear regression by testing hypotheses using F and t. The results showed that partially inflation and interest rates had a negative and insignificant effect on stock returns while the rupiah exchange rate had a positive and significant effect on stock returns. Simultaneously that the variables of inflation, interest rates and exchange rates have a significant effect on stock returns on manufacturing companies that go public on the Indonesia Stock Exchange. The amount of variation in inflation, interest rates and exchange rates is only able to explain variations in stock returns by 4.4 percent, while the remaining 95.6 percent is explained by other variables outside of this research variable.